The Study on Practical Teaching of College and Significant Factors of Student’s Performance in Chengdu, China - Teng, Xu (Scholar: Human Sciences, 2024)
Purpose: This study investigates the factors that influence students’ performance of the practical teaching of Chengdu higher vocational college students, which are determined by perceived usefulness, perceived ease of use, attitude, behavioral intention, social influence, and use behavior. Research design, data, and methodology: The target population was 500 students from Sichuan Vocational College of Finance and Economics, Chengdu Polytechnic, and Chengdu Textile College. The validity and reliability are measured by Item-Objective Congruence (IOC) and Cronbach’s Alpha. Hypotheses were tested using CFA and SEM, and the model’s goodness of fit was validated via SEM. Results: The results show that perceived usefulness significantly influences the attitude of higher vocational students to participate in practical teaching. Behavior intention is influenced by perceived ease of use, perceived usefulness, attitude and social influence. In addition, behavior intention significantly influences use behavior towards student’s performance. Conclusions: The results of this study show that a more active participation attitude, a higher sense of identity in practical teaching, a better understanding of the usefulness and ease of use of practical instruction, a higher social impact, and better student performance are all related to user behavior and willingness of higher vocational students to participate in practical teaching.